Incidental versus clinically evident thyroid cancer: A 5‐year follow‐up study. Issue 3 (24th February 2012) - Minuto, Michele N.; Miccoli, Mario; Viola, David; Ugolini, Clara; Giannini, Riccardo; Torregrossa, Liborio; Antonangeli, Lucia; Aghini‐Lombardi, Fabrizio; Elisei, Rossella; Basolo, Fulvio; Miccoli, Paolo
Abstract Background The incidence of differentiated thyroid cancer in patients undergoing surgery for presumed benign thyroid disease (incidental thyroid cancer) is not negligible. The purpose of this study was to verify if incidental thyroid cancers have a different clinical course than the clinically evident thyroid cancer. Methods A group of patients with incidental thyroid cancer (n = 95) has been compared to a control group with clinically evident thyroid cancer (n = 93). Both the histology and the outcome after a 5‐year follow‐up have been compared. Results At the univariate analysis, the groups demonstrated significant differences in many pathologic features, remnant ablation (p < .001), and persistent disease (p = .006). Nevertheless, the multivariate analysis revealed that the outcome was not influenced by the preoperative or the incidental diagnosis. Conclusion Incidental thyroid cancers show a different pathological pattern when compared to clinically evident thyroid cancers. Nonetheless, the final outcome is not influenced by preoperative or postoperative diagnosis. Hence, patients with incidental thyroid cancer should follow the same postoperative protocols of patients with clinically evident thyroid cancer. © 2012 Wiley Periodicals, Inc. Head Neck, 2013